Identification of Characteristics of Factors That Form Slums in Tanjung Pinggir Village, Pematang Siantar - Angelina Gabriella Sembiring; Dwira Nirfalini Aulia; Wahyuni Zahrah (Journal Of Social Science (JoSS), 2026)
Slum areas remain a critical challenge in urban development, particularly in cities experiencing rapid population growth without adequate housing provision. This study investigates the characteristics and dominant factors contributing to slum formation in Tanjung Pinggir Village, Siantar Martoba District, Pematang Siantar City. The research employed a quantitative descriptive analytical approach with 78 respondents selected through purposive sampling from 347 households. Data were collected through structured questionnaires, field observations, and in-depth interviews and analyzed using descriptive statistics and Principal Component Analysis (PCA) with Varimax rotation. The findings reveal that slums in Tanjung Pinggir Village are characterized by extremely high building density, poor building quality, limited access to basic infrastructure, and inadequate environmental sanitation. Factor analysis identified four dominant contributing factors: basic infrastructure (27.824%), physical condition of buildings (18.671%), environmental sanitation (13.162%), and socioeconomic factors (9.181%). The basic infrastructure factor emerged as the most critical element requiring priority intervention. Proximity to the Final Disposal Site significantly impacts settlement quality through environmental pollution and aesthetic degradation. This study recommends comprehensive and integrated slum management programs focusing on infrastructure improvement—particularly clean water supply, drainage systems, and waste management—alongside community empowerment initiatives to enhance economic capacity and environmental awareness.